Self-reported oral health and access to dental care among pregnant women in Wellington : a thesis presented in fulfilment of the requirements for the degree of Master of Public Health at Massey University, Wellington, New Zealand - Claas, Bianca Muriel (Massey University, 2009)
Pregnancy can have important effects on oral health and pregnant women are a population group requiring special attention with regard to their oral health and their babies? health. International research shows that oral health care for pregnant women has been inadequate, especially in relation to education and health promotion and there is some evidence of disparities by SES and ethnicity. Improving oral health is one of the health priorities in the New Zealand Health Strategy (Ministry of Health, 2000) and the Ministry of Health (Ministry of Health, 2006a) has recently identified a need for more information on the oral health and behaviour of pre-natal women. The aims of this study were to gain an understanding of pregnant women?s oral health care practices, access to oral health care information and use of dental care services and to identify any difference by ethnicity and socio-economic position. A self-reported questionnaire was completed by 405 pregnant women (55% response rate) who attended antenatal classes in the Wellington region. The questionnaire was broadly divided into four parts: (1) care of the teeth when the woman was not pregnant; (2) care of the teeth and diet during the pregnancy; (3) sources of oral health information during pregnancy and; (4) demographic information . Data were analysed by age, ethnicity, education and income and odds ratios (OR) and 95% confidence intervals (95%CI) were calculated using logistic regression. The majority of women in this survey were pakeha (80.2%), compared to 19.7% „Others? (8.8% Maori, 1.9% Pacific, 8.6% other). Most of the subjects were aged 31-35 years (34.5%), of high SES (household income and education level). Half of the women reported having regular visits to the dentist previous pregnancy while a significant percentage of women saw a dentist basically when they had problems. The usual dental hygiene habits were maintained during pregnancy. However, during pregnancy more than 60% of women reported bleeding gums. Just 32% of women went to see the dentist during pregnancy and less than half had access to oral health information related to pregnancy. „Others? (OR 0.38, 95% CI 0.15-0.91) and low income (OR 0.27, 95% CI 0.10-0.76) groups were significantly less likely to report access to oral health information compared to pakeha and high income groups (respectively). Women who went to see the dentist during pregnancy were more likely to receive information on dental health. However, low income women were more likely to report the need to see a dentist (OR 2.55, CI 1.08-5.99). Information on dental health and access to oral care should be prioritised to low income women, Maori, Pacific and other ethnic groups. Little attention has previously been given to oral health for pregnant women in New Zealand and there is a need to increase awareness of the importance of this area amongst health practitioners particularly Lead Maternity Carers and Plunket and tamariki ora nurses.
Keywords: Dental care services; Maternity services; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services